The quantum mechanics in construction - Pinto Neto, Nelson (Cadernos de Astronomia, 2025)
Quantum mechanics was developed in the early 20th century as a computational algorithm to organize and predict the strange results of a wide variety of experiments involving the microscopic world (molecules, atoms, elementary particles), which appeared random but had a predictable probabilistic distribution. Despite its overwhelming success, the conceptual foundations of this algorithm remain unclear and extremely controversial. How can we connect the microscopic world described by quantum mechanics with the macroscopic world of our daily experience? What is the role of observers in this connection? Why don’t strange quantum phenomena occur on macroscopic scales? How can we explain the nonlocal nature of quantum phenomena? In this article I will present some attempts to answer these and other basic questions, which constitute different theories with completely different worldviews, commenting on their strengths and weaknesses. We will conclude that quantum theory is still under construction, as there is no consensual formulation. Its development is a fundamental problem in contemporary physics, and in thought in general.